Mengungkap Simbolisme Warna sebagai Representasi Emosi dalam Inside Out 2 - Ainur Rofiq; Asy Syifa Nur Khasanah; Amanda Qurrota A’yun; Yaqutil Ummi Rohimah; Syamsul Ma’arif (Universitas Palangka Raya, 2024)
The animated film Inside Out 2 continues the interesting story of the dynamics of human emotions represented by emotional characters such as Joy (happy), Sadness (sad), Anger (angry), Fear (fear), Disgust (disgust), and introduces new emotions such as Anxiety (Anxious), Envy (envy), Ennui (boredom), and Embarassment (embarrassed). The film uses distinctive colors in each character to reinforce the emotional message and provide an immersive visual experience to the audience. This study aims to analyze the relationship between color and emotion in Inside Out 2 with a color psychology approach. The method used is qualitative descriptive research with an in-depth analysis of color symbolism and its impact on the audience's perception. The findings of this study reveal that color in animated films is not just a visual element, but a strong emotional language. The colors in the characters and the background of the story are able to influence the audience's psychology, shape the mood, and depict the emotional journey. These findings confirm that color has a hidden power to convey messages, build emotional connections, and strengthen the identity of characters in the story, making the viewing experience more immersive and meaningful.